1999
DOI: 10.1590/s0036-46651999000300008
|View full text |Cite
|
Sign up to set email alerts
|

Serological diagnosis of toxoplasmosis: usefulness of IgA detection and IgG avidity determination in a patient with a persistent IgM antibody response to Toxoplasma gondii

Abstract: SUMMARYWe report the detection of specific IgA antibodies and the determination of IgG avidity in sequential serum samples from a patient exhibiting significant levels of Toxoplasma-specific IgM antibodies for seven years after the onset of the clinical symptoms of toxoplasmosis. IgM antibodies were detected by an indirect immunofluorescence test and by three commercial enzyme-linked immunosorbent assays (ELISA). Anti-T. gondii IgA was quantified by the α-capture ELISA technique using a commercial kit. As defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
5

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 12 publications
1
15
0
5
Order By: Relevance
“…In most cases, the indeterminate patients were negative in our IgM-GIPL ELISA but positive in the commercial IgM tests (IFA and capture ELISA). While the use of low-affinity IgG as being indicative of acute infection with T. gondii is a matter of debate (13,15), different studies indicate that, consistent with our findings, high-avidity IgG antibodies are good indicators of an infection that was acquired in the past (3,4,5,13).…”
Section: Discussionsupporting
confidence: 85%
“…In most cases, the indeterminate patients were negative in our IgM-GIPL ELISA but positive in the commercial IgM tests (IFA and capture ELISA). While the use of low-affinity IgG as being indicative of acute infection with T. gondii is a matter of debate (13,15), different studies indicate that, consistent with our findings, high-avidity IgG antibodies are good indicators of an infection that was acquired in the past (3,4,5,13).…”
Section: Discussionsupporting
confidence: 85%
“…19 More recently, the capture principle has been applied for the detection of other immunoglobulin isotypes such as IgE 20,21 and IgA. 22,23 The binding of a representative part of the total IgE and subsequent detection of anti-P. brasiliensis IgE reflects the relative amount of specific versus total IgE, and not the absolute concentration of specific IgE as measured by indirect ELISA. An increase in the relative amount of specific IgE seemed to be a more sensitive parameter than an increase in the absolute concentration of specific IgE in serum measured by indirect ELISA.…”
Section: Resultsmentioning
confidence: 99%
“…However, kinetic studies revealed that in most cases the decline in the reactivity of IgA antibodies detected by the Platelia test was slower than for IgM antibodies detected by ELISA. Bertozzi et al [8] reported the detection of speci®c IgA antibodies by the ETI-TOXOK-A kit in sequential sera from a patient exhibiting signi®cant levels of T. gondii-speci®c IgM antibodies for 7 years after the onset of the clinical symptoms of toxoplasmosis. Although shorter persistence of speci®c IgA antibodies was observed, signi®-cant levels (.…”
Section: Discussionmentioning
confidence: 99%